Learning Design for Ethnophysics-Integrated Physics: A Study on Parabolic Motion Through Gatrik Game - Liliawati, Winny; Yetia, Yeyet; Suyana, Iyon; Maharani, Ghia Syifa; Danawan, Agus; Zakwandi, Rizki (Mitra Edukasi dan Publikasi, 2025)
Ethnophysics is an innovation in physics learning that connects local culture, traditions, and community practices into learning by analyzing physics concepts that occur. One form of application is through the traditional game Gatrik, which contains the principles of motion, especially parabolic motion. This study aims to design and implement an ethnophysics-integrated physics learning design on parabolic motion material through the Gatrik game. This research uses qualitative method with participatory action research design on the implemented learning process. This research focuses on observing learning with a lesson study approach, which consists of three stages namely plan, do, and see which focus on strengthening and assisting high school physics teachers in developing ethnophysics-based teaching tools. At the plan stage, learning tools were prepared in the form of lesson plans and LKPD; at the do and see stages, open lessons were conducted to observe the implementation of learning. The data in this study were collected using a learning observation sheet, especially at the see stage of a series of lesson study activities. The results of the plan stage are in the form of lesson plans and LKPD that have been adapted to ethnophysics integrated physics learning. Furthermore, the results of observations at the do and see stages show that physics learning that integrates Gatrik games as a representation of ethnophysics can increase student learning activities. Learning combined with traditional games can significantly increase students' enthusiasm for physics material. In general, the integration of ethnophysics in learning can contribute to the preservation of local wisdom and increase students' interest and motivation to learn in Physics.